Levels of mercury in fish-eating children, with and without amalgam restoration - Vinayak Padmakumar; Kavya Premkala Raveendran; Anshad Mohamed Abdulla; Sivadas Ganapathy; Shan Sainudeen; V S Nasim; Vaishnavi Vedam (Wolters Kluwer Medknow Publications, 2019)
Background: Mercury is a naturally occurring metal that exists in three forms: elemental (metallic), inorganic, and organic mercury. Amalgam, which is an alloy of inorganic mercury, is used as a restorative material in dentistry. Organic mercury gets ingested in the body mainly by the consumption of seafood. Mercury is also stated to cause various adverse health effects such as gastrointestinal disturbances, dermatitis, muscle weakness, and neurological disorders. In recent years, the use of amalgam has become a controversy stating the various adverse effects of mercury. Hence, the study was conducted to determine and compare the variation in levels of organic and inorganic mercury in fish-eating children before and after placement of amalgam restoration. Materials and Methods: Seventy-five subjects, 42 males (56%) and 35 females (44%) of age group ranging 7-13 years, living in South Canara district of Karnataka, India, were selected as a part of the study. Hair and urine samples were collected for estimation of organic and inorganic levels of mercury, respectively. Informed consent was collected from all the participating subjects. Results: On comparison between organic and inorganic mercury levels during the study period, the concentration of organic mercury in hair samples was greater irrespective of amalgam restorations present (1.172 and 0.085, respectively; P < 0.001). Conclusion: Thus inorganic levels of mercury do not seem to pose a threat as much as the organic levels observed in hair, which remain fairly constant for a longer period of time. Hence in a coastal region where this study was undertaken and fish being a staple food, the risk could probably be attributed to more of an organic toxicity than an inorganic one. Thus amalgam is relatively safe to be practiced and the controversy against it should be reevaluated.